2017
DOI: 10.1177/0963721416672463
|View full text |Cite
|
Sign up to set email alerts
|

The Math Anxiety-Performance Link

Abstract: Demand for science, technology, engineering, and mathematics (STEM) professionals is on the rise worldwide. To effectively meet this demand, many governments and private organizations have revamped STEM education and promoted training to enhance math and science skills among students and workers. Education and training programs typically focus on increasing individuals’ math and science knowledge. However, data from laboratory studies and large-scale international assessments suggest that fear or apprehension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
178
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(232 citation statements)
references
References 39 publications
3
178
0
10
Order By: Relevance
“…Follow up research should examine whether early performance around spatial relevant tasks contributes to growth in spatial anxiety or whether spatial anxiety derails the student performance outcomes for spatial tasks. Recent research in the comparable domain of math anxiety (e.g., Foley et al, 2017), leads us to theorize that there is likely a bidirectional relation between spatial anxiety and performance on spatial tasks with some work suggesting the ability to anxiety relation is likely stronger than the anxiety to ability relation (Gunderson, Park, Maloney, Beilock, & Levine, 2017;Ma & Xu, 2004;Ramirez, Fries, et al, 2017;Ramirez et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Follow up research should examine whether early performance around spatial relevant tasks contributes to growth in spatial anxiety or whether spatial anxiety derails the student performance outcomes for spatial tasks. Recent research in the comparable domain of math anxiety (e.g., Foley et al, 2017), leads us to theorize that there is likely a bidirectional relation between spatial anxiety and performance on spatial tasks with some work suggesting the ability to anxiety relation is likely stronger than the anxiety to ability relation (Gunderson, Park, Maloney, Beilock, & Levine, 2017;Ma & Xu, 2004;Ramirez, Fries, et al, 2017;Ramirez et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This is an issue that has prevailed for decades despite a vast body of research that has shown the ways to teach mathematics well (Schoenfeld, 2002;Boaler, 2015Boaler, , 2016. Low mathematics achievement is not the only problem that faces the US-math anxiety is widespread among school children and the general population (Ashcraft and Krause, 2007;Foley et al, 2017). Most of the attention that is given to this issue considers the curriculum standards and textbooks used in classrooms.…”
Section: Discussionmentioning
confidence: 99%
“…(Satherley, Lawes, & Sok, 2008, p. 4) However, at the same time as there is growing international demand for science, technology, engineering and mathematics (STEM) professionals, the number of people studying STEM subjects internationally has been on the decline (Fairweather, 2008;Jolly, 2009). Hence, to help better equip students with high levels of mathematics and science, increased attention is being devoted to understanding why some countries are better at advancing mathematics and science achievement than others (Foley et al, 2017).…”
Section: Meaningful Contexts and International Comparative Assessmentmentioning
confidence: 99%
“…It appears that maths anxiety results in measurable changes in the brain -for example, the anticipation of doing mathematics -can cause greater activity in regions of the brain associated with visceral threat detection, and such worries deplete working memory so students either rely on using low-level but safe strategies or tend to make mistakes when using more advanced strategies (Foley et al, 2017). Maths anxious individuals tend to learn less over the year, and can have difficulty with basic maths tasks, whereas a poor grasp of basic tasks may predispose students to develop anxiety (Foley et al, 2017). Such anxiety may also be infectious, in that children interacting mathematically with maths anxious parents or adults show impaired performance (Boaler, 2015c;Foley et al, 2017).…”
Section: Evidence From Research: the Influence Of Affectmentioning
confidence: 99%